Youth sport specialization: How to manage competition and training? - Capranica, L.; Millard-Stafford, M. L. (International Journal of Sports Physiology and Performance, 2011)
A prevailing theory (and practical application) is that elite performance requires early childhood skill development and training across various domains, including sport. Debate continues whether children specializing early (ie, training/competition in a single sport) have true advantage compared with those who sample various sports early and specialize in a single sport later (adolescence). Retrospective data and case studies suggest either model yields elite status depending upon the sport category (ie, situational: ball games, martial arts, fencing; quantitative: track and field, swimming, skiing; or qualitative: gymnastics, diving, figure skating). However, potential risks of early specialization include greater attrition and adverse physical/emotional health outcomes. With the advent of the IOC Youth Olympic Games, increased emphasis on global youth competition has unknown implications but also represents a potential platform for investigation. Modification of youth competition formats should be based upon multidisciplinary research on psycho-physiological responses, and technical-tactical behaviors during competition. The assumption that a simple scaled-down approach of adult competitions facilitates the development of technical/tactical skills of youth athletes is not necessarily substantiated with field-based research. Relatively little evidence exists regarding the long-term effects of rigorous training and competitive schedules on children in specific sports. It is clear that more prospective studies are needed to understand the training dose that optimally develops adaptations in youth without inducing dropout, overtraining syndrome, and/or injury. Such an approach should be sport specific as well as gender based. Until such evidence exists, coaches and sport administrators will continue to rely upon their sport-specific dogma to influence programmatic development of our most vulnerable population.